قياس تكلفة منتجات نحل العسل في محافظة اللاذقية- الأسس والمحددات - علي عفراء (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف هذا البحث لاستنتاج أسس احتساب تكلفة منتجات نحل العسل نظراً لكون تحديد التكلفة الفعلية بمُستوياتها المُختلفة على أُسس سليمة ودقيقة هو نقطة البداية الصحيحة لتحقيق كل أهداف نظم التكاليف - فهي أساس التخطيط ومحل الرقابة ومجال التخفيض، ويترتب على عدم توافر معلومات لتحديد تكاليف المنتجات بصورة سليمة اختيار استراتيجيات تنافسية غير سليمة، واتخاذ قرارات غير سليمة، سواءً كانت متعلقة بتسعير المنتجات أو اختيار تشكيلة المنتجات. تم تحقيق هدف البحث من خلال دراسة تحليلية للدراسات السابقة التي ناقشت الجدوى الاقتصادية لمشاريع إنتاج نحل العسل في بيئات متنوعة، بالإضافة لدراسة ميدانية على المناحل العاملة في محافظة اللاذقية خلال الفترة ما بين الشهر الحادي عشر من عام 2017 وحتى نهاية الشهر الثامن من عام 2018 تم التوصل لمجموعة من الاستنتاجات المتعلقة بمحددات قياس تكلفة منتجات نحل العسل، ومنها: ضرورة الاعتماد على منهج التكلفة المتغيرة عند إعداد قائمة تكاليف منتج العسل، واعتماد الموسم الإنتاجي كفترة لإعداد هذه القائمة، وعدد من الاستنتاجات فيما يتعلق بأسس احتساب اهتلاك أصول المنحل وضرورة اعتبارها تكاليف ثابتة يتم إدراجها ضمن قائمة الدخل عن الدورة المالية التي تنتهي بنهاية المواسم الإنتاجية في 31/ 10 من كل عام. The purpose of this research is to deduce the basis for calculating the cost of honey bee products since the actual costing of various levels on accurate basis is the right starting point for achieving all the goals of the cost systems. Because the actual cost is the basis of planning, control and reduction of that cost. Lack of information to properly determine product cost may cause choosing unhealthy competitive strategies, and make bad decisions, whether it related to product pricing or product selection. The research objective was reached through an analytical study of previous studies that discussed the economic feasibility of honey bee production projects in a variety of environments. In addition, a field study was carried out on the working beekeeping firms in Lattakia governorate during the period between the month of 11/2017 and the end of the month 8/2018. A number of conclusions were reached on the determinants of the cost of honey bee products, including the need to rely on the variable cost approach in preparing the list of honey product costs, the adoption of the production season as a period for the preparation of this list and a number of conclusions regarding the basis for calculating the depreciation of the assets of the honeybees and classified it as fixed cost which must included in the income statement for the financial cycle which ends at the end of the production seasons on 31/10 of each year.